Comparison of reproductive traits of foundresses in a native and an invasive hornet in Europe. (August 2018) - Poidatz, Juliette; Bressac, Christophe; Bonnard, Olivier; Thiéry, Denis
Graphical abstract: Abstract: The population dynamics of annual social hymenoptera such as vespids depend largely on the fertility of the foundresses, which, in turn, is a key factor in the context of biological invasions. The native European hornet Vespa crabro ( Vc ) and the invasive Asian hornet Vespa velutina ( Vv ) have generally similar ecological traits, e.g. nesting and feeding habits, although they differ in colony size, which is higher in Vv . Furthermore, in contrast to Vc, Vv is more specialized in its predatory habits, intensively hunting honey bees at the hive. Comparing the morphological and reproductive traits of two closely related species occupying the same ecological niche, one of which is a native species and the other an alien, can help us to gain an understanding of the invasion process. To this end, we here compare reproductive (ovarian size and maturation, fat level, spermatheca size and sperm stock, fecundity) and morphological traits (head size, weight) of the foundresses of these two hornet species. We observed that ovarian maturation began approximately one month earlier in Vv than in Vc, and that the fat level in the former was lower. We found twice the number of sperm in the mated foundresses of Vv than in those of Vc (more than 100 × 10 3 and less than 50 × 10 3 sperm, respectively), in a 16% smaller spermatheca in Vc . Furthermore, the sperm of Vv was found to be 65% shorter than that of Vc . The precocity and higher potential fecundity of Vv queens may have favoured this species over Vc in terms of predatory behaviour, and thereby contributed to its invasiveness.